Changes in axial length in anisometropic children wearing orthokeratology lenses - Qin, Jian; Qing, Huiling; Ji, Na; Lyu, Tianbin; Ma, Hui; Shi, Menghai; Yu, Shiao; Ma, Conghui; Fu, Aicun (Frontiers in Medicine, 2023)
Purpose There is a particular anisometropia occurring in one eye with myopia, while the other eye has very low myopia, emmetropia, or very low hyperopia. It is unclear how the binocular axial length changes when these children wear unilateral OK lenses only in the more myopic eyes. This study investigates the changes in the axial elongation of both eyes. Methods This is a 1-year retrospective study. In total, 148 children with myopic anisometropia were included. The more myopic eyes were wearing orthokeratology lenses (treated eyes), whereas the contralateral eyes were not indicated for visual correction (untreated eyes). The untreated eyes were classified into three subgroups based on the spherical equivalent refraction (SER): low myopia (≤ -0.50 D, n = 37), emmetropia (+0.49 to −0.49 D, n = 76), and low hyperopia (≥0.50 D, n = 35). Changes in the axial length (AL) were compared between the untreated and treated eyes and among the three subgroups. Results The axial elongation was 0.14 ± 0.18 mm and 0.39 ± 0.27 mm in all treated and untreated eyes, respectively (p < 0.001). The interocular AL difference decreased significantly from 1.09 ± 0.45 mm at the baseline to 0.84 ± 0.52 mm at 1 year (p < 0.001). The baseline median (Q1, Q3) SER of the untreated eyes were −0.75 D (−0.56, −0.88 D), 0.00 D (0.00, −0.25 D), and +0.75 D (+1.00, +0.62 D) in low myopia, emmetropia, and low hyperopia subgroups, respectively. The axial elongation was 0.14 ± 0.18 mm, 0.15 ± 0.17 mm, and 0.13 ± 0.21 mm (p = 0.92) in the treated eyes and 0.44 ± 0.25 mm, 0.35 ± 0.24 mm, and 0.41 ± 0.33 mm in the untreated eyes (p = 0.11) after 1 year. Multivariate linear regression analyses only showed significant differences in axial elongation between the emmetropia and low myopia subgroups of untreated eyes (p = 0.04; p > 0.05 between other subgroups). Conclusion Unilateral orthokeratology lenses effectively reduced axial elongation in the more myopic eyes and reduced interocular AL differences in children with myopic anisometropia. The refractive state of the untreated eyes did not affect the axial elongation of the more myopic eye wearing the orthokeratology lens. In the untreated eyes, AL increased faster in the low myopia subgroup than in the emmetropia subgroup.